ЎҚИТУВЧИ ШАХСИ СТРУКТУРАСИДА ПЕДАГОГИК АРТИСТИЗМНИНГ АҲАМИЯТИ - Пиримбетов, Б.А. (SCIENCE and SOCIETY, 2022)
In this article there is presented pedagogical skill, its structure and functions, as well as its role in the structure of the teacher's personality; the purpose, tasks and results of the work of the teacher-artist. It also analyzes internal and external artistry, the components of pedagogical artistry, the roles that it performs.
Keywords: professional activity; science; lesson; pedagogical art; pedagogical creativity; pedagogical skills; pedagogical tactics; pedagogical technique; continuous education; pedagogical process